The model of morphosemantic patterns in the description of lexical architecture - Raffaelli, Ida (2013)
The paper presents a model of morphosemantic patterns based on the model of Guiraud’s morphosemantic fields. The main reason for introducing this model into the description of the architecture of the Croatian lexicon is the fact that Croatian is a morphologically rich language, in which grammatical and semantic mechanisms interact in lexical organization. The model of morphosemantic patterns at this stage of its development consists of two basic models: the model of morphosemantic fields and the model of morphosemantic grounds. Although the model is based on structuralist tenets, it is our intention to demonstrate how it is related to some of the most prominent contemporary theoretical frameworks, namely Cognitive Linguistics and Construction Grammar, especially Construction Morphology.
Projekt MZOS
ENG